PERKEMBANGAN IMPLEMENTASI PENDIDIKAN INKLUSI - Yulia Anjarwati Purbasari; Wiwin Hendriani Hendriani; Nono Hery Yoenanto (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2022)
This literature study aims to reveal the extent to which the development of the implementation of inclusive schools in Indonesia. Selected articles through screening were taken from the E-Journal of education, inclusive education, and psychology journals under the Ministry of Research, Technology and Higher Education with limited publication years 2016-2021. The initial search found 140 journals that were selected by applying the criteria for inclusion of Indonesian education and children with special needs so that there were 15 journals consisting of 10 qualitative journals, 1 journal of mixed methods, 1 journal of national seminar proceedings, and 3 thesis theses. Based on the review, it was found that the results of implementing inclusive education still experience many challenges and obstacles. Among them in terms of teacher competence, facilities and infrastructure, curriculum modification for heterogeneous children, evaluation, parental involvement, and the level of cooperation with related parties. This can be a reference for the government to pay more attention to inclusive education so that it can provide the right to a proper education for every Indonesian child.